1944
DOI: 10.1002/hlca.194402701189
|View full text |Cite
|
Sign up to set email alerts
|

Über die Hydroxychloride des Magnesiums

Abstract: 1. Beim Umsetzen von Magnesiumoxyd in Magnesiumchloridlösung konzentrierter als 1,25‐m. bilden sich zwei wohldefinierte Hydroxychloride mit charakteristischem Röntgendiagramm. Zuerst bildet sich bei allen Konzentrationen die instabile Verbindung 1 MgCl2, 5 Mg(OH)2, 7 H2O; diese wandelt sich nachträglich in die bei allen Konzentrationen stabile Verbindung 1 MgCl2, 3 Mg(OH)2, 7 H2O um.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

1949
1949
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 7 publications
1
26
0
2
Order By: Relevance
“…The 5:1 oxychloride was not present (according to the X-ray patterns) at 1 day in the more concentrated MgClz solutions and remained at 7 months in the most dilute in which it was formed. Lukens [2] found that in 71-percent MgCI2·6H zO solutions the 5: 1 compound formed first, and Feitknecht and Held [6] found it was that precipitated first and subsequently converted to the 3:1 compound at all con centrations above about 27.S percent of MgCb·6HzO. In the present work when the oxychloride precipitates were transferred to fresh solutions containing no MgO, these solutions became supersaturated (i n terms of _ MgO) with respect to their final concentrations.…”
Section: Precipitation Of Magnesium Oxychloridesupporting
confidence: 45%
See 3 more Smart Citations
“…The 5:1 oxychloride was not present (according to the X-ray patterns) at 1 day in the more concentrated MgClz solutions and remained at 7 months in the most dilute in which it was formed. Lukens [2] found that in 71-percent MgCI2·6H zO solutions the 5: 1 compound formed first, and Feitknecht and Held [6] found it was that precipitated first and subsequently converted to the 3:1 compound at all con centrations above about 27.S percent of MgCb·6HzO. In the present work when the oxychloride precipitates were transferred to fresh solutions containing no MgO, these solutions became supersaturated (i n terms of _ MgO) with respect to their final concentrations.…”
Section: Precipitation Of Magnesium Oxychloridesupporting
confidence: 45%
“…The assoc iated valu e of n is consider ed to beS in t he ma terialas precipi tated. F ei t knecht and Hrld [6] fo und n to be for their preparation after washing and dryin g. but thi s value was not approach ed wi th t he 5: 1 compound in the present wo rk 3.4…”
Section: H Eals Of Solulion Of 3:\1 G (Oh ) · ~I Gc I 2 ' H20mentioning
confidence: 53%
See 2 more Smart Citations
“…These curves show that the 50-day heat of hardenin g of mixtures containing large amounts of MgO is less than the h eat of hydration of MgO to Mg (OH)2, 224 callg of MgO. It bas been shown, [9] that unrcacted magnesia may remain in magnesium oxychloride pastes after hardening. The pastes studied here were in sealed containers, so that no hydration subsequent to hardening could be caused by moisture from the atmosphere,…”
Section: 2 Heat·of-solution Measurementsmentioning
confidence: 94%